Hybrid coating prepared with PMMA/Ti-O-Si tested under vacuum conditions for use in nanosatellites. - Bryanda G Reyes-Tesillo; Genoveva Hernández-Padrón; Jorge A Ferrer-Pérez; Alfredo Maciel-Cerda (PLoS ONE)
A hybrid coating made of poly (methyl methacrylate) with SiO2-TiO2 particles (PMMA/SiO2-TiO2) has been developed for use as a coating on nanosatellites, evaluating its resistance to high vacuum by quantifying its weight loss. The coating was applied on an Al 7075 aluminum substrate used for the aerospace sector. PMMA/SiO2-TiO2 hybrid coatings were prepared using sol-gel reaction in situ assisted with sonochemistry. The SiO2 particles and TiO2 (50:50% wt. of rutile/anatase) particles by tetraethyl orthosilicate (TEOS), and Titanium (IV) Isopropoxide (TIPO). Radical polymerization of methyl methacrylate (MMA) monomer was conducted with (3-mercaptopropyl) trimethoxy silane (3-MPTS) used as a coupling molecular agent, and benzoyl peroxide as a catalyst. The coatings obtained have a thickness of 20 μm which were deposited by blade coating technique on the substrate, obtaining homogeneous and defect-free coatings. Adhesion and hardness were measured using ASTM standards required for this sector. To evaluate its resistance to ultra-high vacuum, it was done as close as possible to the ASTM E-595 norm [1], where it indicates that the coatings must be evaluated at vacuum conditions of 10-5 Torr and 125°C for a period of 24 hours. The coatings were evaluated before and after the test by spectroscopy analysis to determine a possible degradation in the chemical structure. The resulting weight loss not exceeding 0.02%, and the addition of Ti-O-Si particles led to an increase in chemical stability under vacuum conditions without affecting the chemical structure of the highly cross-linked PMMA/Ti-O-Si matrix, which was monitored by FTIR and Raman spectroscopy.